Corporate parenting in the classroom - Bruce Adamson (Scottish Journal of Residential Child Care)
This speech by Bruce Adamson, Children and Young People's Commissioner was delivered at the CELCIS Conference: 'Corporate Parenting in the Classroom' in March 2018. It sets out the relevant human rights framework and emphasises the international duties placed upon the State to uphold the rights of care experienced children and young people. Mr Adamson reflects on his recent experience at Care Day 2018 and highlights the voices of care experienced young people. The right to education to develop children and young people to their fullest and the support that needs to be put in place for children, young people and teachers to be able to focus on education. The Commissioner explains the role of his office in promoting and safeguarding rights, holding government to account, his particular remit for care experienced children and young people and his office’s collaborative work with corporate parents. He concludes with the crucial role of those who work in education to empower and support children and young people to defend their rights and the rights of others.